Morphological characteristics of okra fruits [Abelmoschus esculentus (L.) Moench.] cultivated in the dry tropic (Agro Productividad, 2021)
Objective: The objective was to evaluate the morphological characteristics of okra fruit[Abelmoschus esculentus (L.) Moench.], an endemic crop of the Afro-Mexican region, inthe dry tropics.Design/Methodology/Approach: Materials were collected in Cuajinicuilapa, in thestate of Guerrero in Mexico. Using a completely randomized design (CRD), 4 repetitionsof 100 fruits were selected, and each was evaluated for the following: weight, number,size and shape of fruits and seeds. Data were analyzed using measures of centraltendency, utilizing SAS.Results: The fruits are heterogeneous and some are deformed, they have a long andfluted shape, with an average weight of 10.4 g and 95 seeds each weighing 0.05 g. Theseeds are round with a conical micropyle, the testa is dark grey, and the embryo white.Study Limitations/Implications: It is necessary to keep studying the morphologicalcharacteristics of okra fruit for a longer period of time and to establish farming in orderto widen the outlook of decision making.Findings/Conclusions: Okra fruits from backyard farming have better quality andpotential for fresh or processed consumption. There is a lack of management andimprovement of this crop.